Reframing viral infections as acute metabolic disorders: dengue viruses and their dependency on host metabolic pathways - St. Clair, Laura A., author; Perera, Rushika, advisor; Belisle, John, committee member; Nachappa, Punya, committee member; Wilusz, Jeff, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2022)
Dengue viruses (DENVs) are the etiological agent of the world's most aggressive arthropod-borne disease. At present, there are no available antivirals against DENVs. This fact underscores a dire need to examine host-virus interactions to identify and develop novel therapeutic approaches. As obligate intracellular parasites, DENVs are reliant upon and hijack several host metabolic pathways both to fulfill their replicative needs, and to evade the host immune response. We and others have previously established that infection with DENVs causes significant perturbation to host lipid metabolism, including elevations in sphingolipids in both the human and mosquito host. In addition, we and others previously discovered that the DENV NS1 protein increases sialidase activity in both in vitro and in vivo models leading to increased endothelial hyperpermeability and vascular leakage which are hallmarks of severe dengue. To further clarify and characterize these previous works, we have performed siRNA-mediated loss of function studies using human hepatoma cells (Huh7 cells) on several metabolic pathways altered during DENV2 infection. First, we examined the role of acyl-CoA thioesterases, enzymes responsible for controlling the intracellular balance of activated fatty acids and free fatty acids, on the DENV2 lifecycle. In these analyses, we determined that the cytosolic ACOT1 enzyme had an inhibitory effect on DENV2 replication and release, while mitochondrial ACOT (ACOTs 2 and 7) functionality was critical for viral replication and release. Moreover, we identified several enzymes within the ACOT family whose expression was dependent on ACOT2 and ACOT7 expression. These results highlighted complex relationships between ACOTs and DENVs, as well as identified yet unknown functional interdependence between ACOT enzymes. Next, we expanded our previous understanding of the relationship between DENVs and the human sialidase enzymes (NEU1-4). While previously studies linked upregulation of these enzymes with DENV2 pathology, we provide the first evidence showing that NEU1-4 functionality is vital for DENV2 genome replication and viral egress. Moreover, our analyses also revealed previously unknown functionality of NEU4 or its downstream products as transcriptional regulators for NEU1-3. Finally, we provide the first profile of the effect of loss of function of enzymes within the entire sphingolipid metabolic pathway (as identified through KEGG pathway database) on the DENV2 life cycle. In this study, we identified that enzymes involved the sphingomyelinase and salvage pathways of ceramide synthesis as opposed to de novo ceramide synthesis were critical to DENV2 release from Huh7 cells. In addition, we determined that enzymes involved in the synthesis and degradation of glycosphingolipids were vital for DENV2 release. An especially intriguing result within this arm of sphingolipid metabolism was that the two enzymes which hydrolyze GluCer had differential effects on DENV2 replication and release. GBA1 (lysosomal) had an antiviral effect on DENV2, while GBA2 (non-lysosomal) was required for DENV2 replication and release. This prompted us to profile the changes that occur to glycosphingolipids (GSLs) during infection, and we uncovered several species of GSLs that are elevated during infection. Moreover, we identified that Ambroxol HCl, a pharmaceutical GBA1 chaperone/GBA2 inhibitor, was able to abrogate these elevations in GSLs. Combined, our results allowed us to propose a novel function for GBA2 as a GluCer recycling enzyme during DENV2 infection. In conclusion, together, the work in this dissertation highlights critical metabolic nodes that impact virus replication and provides new directions for investigating viral infections as acute metabolic diseases.
Keywords: glycosphingolipids; neuraminidase; thioesterase; metabolism; dengue; sphingolipids